Pengawasan Akuntabilitas Pemerintah Daerah terhadap Anggaran Pendapatan dan Belanja Daerah (APBD) - Ellsa Lettryana Hasis; Ida Bagus Anggapurana Pidada (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This study evaluates the supervision and law enforcement regarding the accountability of the local government of Klungkung Regency towards the Regional Budget (APBD). The findings indicate that despite existing regulations governing the framework of supervision and the obligations of local governments, law enforcement still faces several challenges such as regulatory ambiguity and resource constraints. To enhance effectiveness, there is a need for capacity building of supervisory and law enforcement agencies, strengthening inter-agency cooperation, and safeguarding institutional independence. These efforts are crucial to ensuring good and accountable governance of regional finances.